India’s Entrepreneurial Awakening: Navigating Geopolitical Shifts and Domestic Policy Reforms - Ramesh Soni; Kurt Schimmel; Frederick Slack; Jeananne Nicholls (Administrative Sciences)
This paper examines the intersection between entrepreneurship government policy and managerial theory. The context chosen for this study is India. India has experienced a significant global geopolitical shift that is coinciding with India’s domestic policy reforms and notable domestic initiatives. Since 2014, India’s entrepreneurial ecosystem has seen a significant increase in the number of startups and unicorns. This paper presents arguments that the confluence of global realignments, such as the diversification of supply chains away from China and increasing interest in the Indo-Pacific region, along with domestic initiatives like “Make in India”, “Startup India”, and digitalization drives, along with massive investments in infrastructure improvements, have made India a desirable destination for entrepreneurial activity. By examining these factors through the lens of three theories—resource-based view, global value chain, and innovation ecosystem theory—this paper identifies key opportunities and challenges for entrepreneurs across various sectors. It is hoped that this research will contribute to a deeper understanding of India’s evolving entrepreneurial landscape. In addition, entrepreneurs, policymakers, and investors can benefit from this article to understand the opportunities and challenges India poses in order to contribute to India’s continued economic growth and its emergence as a global entrepreneurial powerhouse. Finally, this paper helps to bridge the gap between economic policy and management theory.